The DESIGN AND DEVELOPMENT OF EFFECTIVE DISTANCE MEASUREMENT ON BOLAWRAP EQUIPMENT PERSONNEL IN PERFORMING TASKS - Febrianto, Rohman; Santoso , Rahmad; Fitriani, Indah Martha (Pustaka Poltekad, 2021)
Abstract - Various threats that occur in the field are a problem for individuals who are faced with human rights law where personnel must make decisions quickly and accurately, the innovation of the Bola wrap weapon can paralyze the enemy without injuring the enemy by firing Kevlar ropes to bind the enemy unable to move optimally. The researcher used the experimental method to get the results that confirm the causal relationship between the variables designed, research and develop a basic circuit by determining the effective firing range of the Bola wrap, we use the Sharp Gp2y0a710k0f sensor as an effective sensor measuring distance with a maximum range of 550 cm, the distance detected by the Sharp Gp2y0a710k0f sensor. will be processed by Arduino nano as a programming controller whose output will be displayed on the Oled LCD according to the Sharp Gp2y0a710k0f sensor in the form of a light emitting diode (LED) as an indicator, the solenoid will open the trigger with an effective firing range, and laser as a point shot. From the target, the Bola wrap weapon uses 9mm caliber munitions as a Kevlar rope projectile amplifier to bind enemies or rebels, from the results of the research it can open a predetermined lock between a range of 200 cm - 500 cm which is displayed on the Oled LCD, and the green indicator light and the Solenoid are open. The trigger will help optimally in shooting Bola wrap to paralyze enemies or rebels from moving optimally, Bola wrap weapons are used as personnel equipment in carrying out the main tasks of achieving TNI tasks effectively and optimally.